2012
DOI: 10.1111/j.1754-4505.2012.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of the oral health‐related quality of life of autistic children in Saudi Arabia

Abstract: The aim of this study was to use parental perception to assess the Oral Health Related Quality of Life (OHRQoL) of children with Autism. A total of 59 families of children with Autism who had an unaffected sibling were cross-matched for age and gender of the affected child with families with no autistic children. The parents were administered the Parental Perception Questionnaire (P-CPQ) and the Family impact scale (FIS) components of and Arabic version of the Child Oral Health Related Quality of Life question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 28 publications
9
77
1
2
Order By: Relevance
“…Section 2 of the questionnaire focuses on the signs and symptoms the child experiences due to his oral health condition. The mean score was 19.70 (SD 8.79), which compares very well with that reported in another study using the same tool (21.02 ± 18.14) [23]. Section 3 of the questionnaire focuses on the effects of oral health status on children's feelings and everyday activities while section 4 focuses on the effects of oral health on parents and other family members.…”
Section: Oral Health and Quality Of Lifesupporting
confidence: 71%
See 1 more Smart Citation
“…Section 2 of the questionnaire focuses on the signs and symptoms the child experiences due to his oral health condition. The mean score was 19.70 (SD 8.79), which compares very well with that reported in another study using the same tool (21.02 ± 18.14) [23]. Section 3 of the questionnaire focuses on the effects of oral health status on children's feelings and everyday activities while section 4 focuses on the effects of oral health on parents and other family members.…”
Section: Oral Health and Quality Of Lifesupporting
confidence: 71%
“…More recently, a number of oral-health-related quality of life (OHRQoL) scales have been developed and validated [23]. As children-very young children, in particular-are often not reliable sources of information for medical purposes (e.g., diagnosis), parents are relied on as informants for measuring child OHRQoL [22].…”
Section: Pilot Program Implementation and Assessmentmentioning
confidence: 99%
“…Approximately one-third of the studies considered for inclusion [4,25,26,28,32,33,38,43], [47,48,50] were published in 2013, while eight [14,21,27,29,31,34,35,83] and six papers [15,22,30,40,44,52] were published in 2012 and 2011 respectively. Aside from one paper published in 2005 [49], there were no papers that pre-dated 2007.…”
Section: Resultsmentioning
confidence: 99%
“…In our study the father's level of education was found to be significantly associated with the dental caries experience in their children. Other two studies [15]; have found that the mother's level of education influence oral health related quality of life of their children but not the father's [16]. The differences in parental roles in those countries may be responsible for these results.…”
Section: Discussionmentioning
confidence: 91%